15 Ovarian germ cell tumours; experience of a regional centre. (1st December 2018) - Cartwright, Douglas; Waterston, Ashita; White, Jeff
Abstract: Introduction: Ovarian germ cell tumours are rare but aggressive cancers which have histological and treatment similarities with the more common male germ cell tumours. However the outcomes are poorer for women with germ cell tumours than for men. 1 Historically, in the west of Scotland, female germ cells patients were managed within standard gynaecological cancer services and male patients in a dedicated germ cell unit. Due to the highly specialised nature of the condition and the experience of the clinicians using similar chemotherapy regimens, the management of ovarian germ cells was incorporated into the germ cell unit. We present the experiences of this unit over the last 6 years. Method: We reviewed data from all women with ovarian germ cell tumours treated or followed up under the regional germ cell unit. Fertility is an important consideration for these young women and we investigated the rate of fertility sparing surgery, utilisation of pre-chemotherapy fertility treatments and the rate of successful pregnancies. With the Introduction of the Cisplatin, Vincristine, Methotrexate, Bleomycin with alternate Actinomycin, Cyclophosphamide and Etoposide chemotherapy regimen (POMB/ACE) there was a concern that this will cause problems with monitoring during treatment as it associated with elevation of alpha fetoprotein (AFP) levels which is used as a marker or response. We compared AFP levels between POMB/ACE and the bleomycin, etoposide, cisplatin (BEP) regimen used in the adjuvant or neo-adjuvant setting. Results: 26 patients have been treated or followed up by the unit over the last 6 years. Median follow up is 55 months (range 3 months – 31 years). The all-cause mortality is 0 and the relapse rate is 19%. Relapses were spread equally through the treatment groups. 21 out of 24 eligible patients received fertility sparing surgery. Of these there has been 6 successful pregnancies following treatment. There was no significant difference in AFP levels between BEP and POMB/ACE groups. Conclusions: Outcomes for ovarian germ cell patients in the west of Scotland are comparable to published case series. The low incidence makes it difficult to identify statistically significant differences however we hope to promote collaboration and gather more data through a national ovarian germ cell database set up through the Scottish Germ Cell Group. Reference: Murugaesu N, Schmid P, Dancey G, Agarwal R, Holden L, McNeish I, et al . Malignant ovarian germ cell tumors: Identification of novel prognostic markers?and long-term outcome after multimodality treatment. J Clin Oncol2006;24:4862–6.